International copyright regulation and the music industry. - NURSE, Keith (1996)
Notes that many countries which were not party to the Berne Convention have been brought into copyright law under the WTO framework. Lists the main additions to the area of copyright as it relates to music and related rights. Identifies the likely impact of the new copyright laws and trends in the marketplace on developing countries as (1) additional administrative and enforcement costs, (2) increased payments for foreigners' proprietary artistic work, (3) price increases associated with greater market power for copyright producers and (4) enchanced protection and collection of copyright royalties for developing countries.